Ocular injuries by less-lethal weapon: a view from Switzerland - Anna Fierz (Torture)
Dear Editor-in-chief: Thank you for focussing on this troubling subject in your issue 1/2024. It confirms that many of the difficulties involved are similar worldwide. Countries that use less-lethal weapons include Switzerland, the only Western European democracy besides France to employ multiple kinetic impact projectiles. Our rubber scattershot is comparatively small and light but has led to an uninterrupted series of severe eye injuries since 1980. Legal authorities have long questioned whether these were due to rubber ammunition, though ophthalmologists always knew what was going on. Communication channels were non-existent, and monitoring remains a challenge. Please see my recent open-access review in Eye (Fierz, 2024) for details. I would like to add the odd point to your commendable editorial (Pérez-Sales et al., 2024). The common denominator is that eye injuries require eye doctors.